Vodou en vogue: fashioning Black divinities in Haiti and the United States - Nwokocha, Eziaku Atuama (Where religion lives, 2023)
"In Haitian Vodou, spirits impact Black practitioners' everyday lives, tightly connecting the sacred and the secular. As Eziaku Atuama Nwokocha reveals in this richly textured book, that connection is manifest in the dynamic relationship between public religious ceremonies, material aesthetics, bodily adornment, and spirit possession"--